Flower-inducing technology facilitates speed breeding in cassava - Rodrmguez, Erika Paola Barinas; Morante, Nelson; Salazar, Sandra; Hyde, Peter T.; Setter, Tim L.; Kulakow, Peter; Aparicio, Johan Steven; Zhang, Xiaofei (Frontiers in Plant Science, 2023)
Cassava is a tropical crop that provides daily carbohydrates to more than five million people. New cassava varieties with improved yield, disease resistance, and food quality are critical to end hunger and reduce poverty in the tropics. However, the progress of new variety development has been dragged down by difficulties in obtaining cassava flowers and making designed crosses. Inducing early flowering and increasing seed production are crucial steps to improving the efficiency of developing farmer-preferred varieties. In the present study, we used breeding progenitors to evaluate the effectiveness of flower-inducing technology, including photoperiod extension, pruning, and growth regulators. All 150 breeding progenitors showed significantly earlier flowering under photoperiod extension, especially for the late-flowering progenitors, reduced from 6-7 months to 3-4 months. Pruning should be combined with growth regulators to increase the seed production. The combination of photoperiod extension, pruning and 6-Benzylaminopurine (synthetic cytokinin) produced significant higher number of fruits and seeds than only photoperiod extension and pruning. Another growth regulator, silver thiosulfate, commonly used to block the action of ethylene, did not show significant effect in fruit or seed production when combined with pruning. The present study validated the protocol for flower inducing in cassava breeding programs and discussed the considerations of implementing the technology. Inducing early flowering and increasing seed production helped move one step further for speed breeding in cassava.